2013
DOI: 10.1186/1471-2164-14-583
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide gene expression profiling of stress response in a spinal cord clip compression injury model

Abstract: BackgroundThe aneurysm clip impact-compression model of spinal cord injury (SCI) is a standard injury model in animals that closely mimics the primary mechanism of most human injuries: acute impact and persisting compression. Its histo-pathological and behavioural outcomes are extensively similar to human SCI. To understand the distinct molecular events underlying this injury model we analyzed global mRNA abundance changes during the acute, subacute and chronic stages of a moderate to severe injury to the rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 117 publications
3
59
0
Order By: Relevance
“…From the long-term observation of 3D images, we found that the vascular density of compression group had no significant different compared with that of the sham group at the 70th day. A few of studies showed that compensatory mechanisms and angiogenesis might exist in chronic compressive spinal cord injury [17,22]. These mechanisms could be useful to explain the alteration of integral vascular network at different time after spinal cord compression.…”
Section: Discussionmentioning
confidence: 99%
“…From the long-term observation of 3D images, we found that the vascular density of compression group had no significant different compared with that of the sham group at the 70th day. A few of studies showed that compensatory mechanisms and angiogenesis might exist in chronic compressive spinal cord injury [17,22]. These mechanisms could be useful to explain the alteration of integral vascular network at different time after spinal cord compression.…”
Section: Discussionmentioning
confidence: 99%
“…Rat and Axolotl microarray data: Rat T7 spinal clip compression injury (7 days) microarray (14) was obtained from GEO-NCBI (goo.gl/Hz4Gj9). Axolotl mexicanum spinal cord injury microarray (9) data was obtained from the same server (goo.gl/Eoshgn).…”
Section: Methodsmentioning
confidence: 99%
“…In rats sustaining a compression SCI, gene expression profiling showed an increase in TLR expression that persisted into the chronic stages, albeit less pronounced than in the acute phase (Chamankhah et al, 2013).…”
Section: Expression Of Tlrs In the Injured Spinal Cordmentioning
confidence: 96%